PENDAMPINGAN PENGGUNAAN CURIPOD SEBAGAI INOVASI PEMBELAJARAN BERBASIS TEKNOLOGI - Rini Fadhillah Putri; Rizqy Fadhlina Putri (LPPI UMN AL WASHLIYAH, 2026)
The community service partner in this program is the SAS ANA Group Foundation, a non-formal educational institution located at Jalan Bilal No. 82, Pulo Brayan Darat I Village, Medan Timur District, Medan City. The partner faces challenges due to limited knowledge of digital learning applications and a lack of skills in utilizing digital technology for teaching and learning activities. As a result, tutors still apply conventional teaching methods by relying primarily on PowerPoint as a learning medium, even though many digital learning applications are available that can better attract students' attention and encourage them to become more active and interactive participants in the learning process. One such application is Curipod. Initial observation data revealed that 72% of the partners still experienced difficulties in using digital applications in learning activities. Keywords : Curipod, Digital Learning